Fourth branch of arch of aorta and its clinical implication - Gitte, Rashmi N; Ganji, Chenna Reddy; Salve, Vishal M (Journal of Biomedical Sciences, 2016)
In human beings the most common branching pattern of the aortic arch was its division into three great vessels ie the brachiocephalic trunk, left common carotid artery and the subclavian artery. The vertebral arteries arise from the superior aspect of the first part of the subclavian artery. In present case, a left vertebral artery arose from the aortic arch as fourth branch was found. The diameter of left vertebral artery at its origin was 6 mm as compared to the right vertebral artery, which has diameter of 3.5 mm at its origin. In this case left sixth dorsal intersegmental artery might have persisted as first part of vertebral artery hence left vertebral artery arising from arch of aorta. Knowledge of the variations in branching pattern of the aortic arch is important in the diagnosis of intracranial aneurysm after subarachnoid haemorrhage.J. Biomed. Sci. 2015, 2(3):21-23.